2012
DOI: 10.1371/journal.pone.0036008
|View full text |Cite
|
Sign up to set email alerts
|

The Hetero-Hexameric Nature of a Chloroplast AAA+ FtsH Protease Contributes to Its Thermodynamic Stability

Abstract: FtsH is an evolutionary conserved membrane-bound metalloprotease complex. While in most prokaryotes FtsH is encoded by a single gene, multiple FtsH genes are found in eukaryotes. Genetic and biochemical data suggest that the Arabidopsis chloroplast FtsH is a hetero-hexamer. This raises the question why photosynthetic organisms require a heteromeric complex, whereas in most bacteria a homomeric one is sufficient. To gain structural information of the possible complexes, the Arabidopsis FtsH2 (type B) and FtsH5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
(75 reference statements)
1
22
0
1
Order By: Relevance
“…Thus, the thylakoid enzyme from C. reinhardtii shows a similar but simpler subunit composition than its counterpart from Arabidopsis, which assembles four distinct FtsH isoforms. We cannot exclude that some FtsH1 and/or FtsH2 may form homohexamer complexes, although homomeric structures are thought to be less likely to exist since they are less stable, as modeled by Moldavski et al (2012).…”
Section: Discussion the Thylakoid Ftsh Protease Of C Reinhardtii Formentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the thylakoid enzyme from C. reinhardtii shows a similar but simpler subunit composition than its counterpart from Arabidopsis, which assembles four distinct FtsH isoforms. We cannot exclude that some FtsH1 and/or FtsH2 may form homohexamer complexes, although homomeric structures are thought to be less likely to exist since they are less stable, as modeled by Moldavski et al (2012).…”
Section: Discussion the Thylakoid Ftsh Protease Of C Reinhardtii Formentioning
confidence: 99%
“…Transformation of these strains with an empty vector (pSL18) did not change their fluorescence kinetics, demonstrating that the FTSH1 gene alone was sufficient for complementation. Thylakoid FtsH proteases form various heterohexamers in cyanobacteria (Boehm et al, 2012) and Arabidopsis (Sakamoto et al, 2003;Yu et al, 2004;Zaltsman et al, 2005;Moldavski et al, 2012). Whereas four isoforms of thylakoid FtsH were identified in Arabidopsis (Zaltsman et al, 2005), only two thylakoid isoforms, FtsH1 and FtsH2, have been identified by proteomic studies in C. reinhardtii (Allmer et al, 2006).…”
Section: Map-based Cloning Of the Point Mutation Ftsh1-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the close evolutionary relationship between cyanobacteria and chloroplasts, it seems reasonable that the hetero-oligomeric complexes found in chloroplasts also contain three of each type of subunit arranged in an alternating fashion around the ring. However, recent work has concluded that chloroplast FtsH heterocomplexes might be composed of two type A and four type B subunits, but deviations from a 1:1 stoichiometry because of contamination by FtsH monomers or partially assembled FtsH complexes could not be excluded (Moldavski et al, 2012). The single-particle approach described here helps overcome this potential problem.…”
Section: Discussionmentioning
confidence: 99%
“…The stoichiometry of type A to type B subunits in an FtsH complex is estimated as 2:4 (Moldavski et al, 2012), whereas the cyanobacterial prototype comprises type A and B subunits in a 3:3 ratio with an alternating arrangement (Boehm et al, 2012). FtsH2 and FtsH5 are targeted to the thylakoid via the TAT (for twin-Arg translocation) pathway and the SEC (for secretion) pathway, respectively (Rodrigues et al, 2011).…”
Section: Ftshmentioning
confidence: 99%